2016
DOI: 10.1186/s12941-016-0125-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenic profile of methicillin-sensitive and resistant Staphylococcus aureus isolated from special groups

Abstract: BackgroundStaphylococcus aureus is characterized by its pathogenicity and high prevalence, causing disease in both healthy and immunocompromised individuals due to its easy dissemination. This fact is aggravated by the widespread dissemination of S. aureus carrying toxigenic genes. The objective of this study was to determine the toxigenic profile of methicillin-sensitive S. aureus (MSSA) and methicillin-resistant S. aureus (MRSA) in patients with purulent skin and/or soft tissue infections seen at the Dermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…As mentioned prior, S. aureus virulence is mainly due to toxin production and is intimately tied to QS. However, not all S. aureus strains have the same toxin profile, as major inter-strain heterogeneity with respect to genetic presence/absence and relative expression of toxin-producing genes is apparent [68,69]. Carlson used various S. aureus strains with different toxin profiles in her initial studies of C. albicans – S. aureus synergism, focusing on toxic-shock syndrome (TSS)-associated isolates and non-TSS disease-associated isolates [70].…”
Section: Candida Albicans and Staphylococcus Aureus: Co-conspiratorsmentioning
confidence: 99%
“…As mentioned prior, S. aureus virulence is mainly due to toxin production and is intimately tied to QS. However, not all S. aureus strains have the same toxin profile, as major inter-strain heterogeneity with respect to genetic presence/absence and relative expression of toxin-producing genes is apparent [68,69]. Carlson used various S. aureus strains with different toxin profiles in her initial studies of C. albicans – S. aureus synergism, focusing on toxic-shock syndrome (TSS)-associated isolates and non-TSS disease-associated isolates [70].…”
Section: Candida Albicans and Staphylococcus Aureus: Co-conspiratorsmentioning
confidence: 99%
“…Distribution of agr types according to MSSA and MRSA isolates but detected the eta gene in only one the MRSA (n=30) isolate. de Souza et al(35) did not find the eta and etb genes in any of MRSA isolates, but detected the eta gene in only 2.3% (3/130) of the MSSA isolates. Similarly, Nhan et al(36) reported a low prevalence rate for eta (1/1186) among clinical S. aureus isolates.…”
mentioning
confidence: 92%
“…It occurs due to modifications of its binding site for the altered Penicillin Binding Protein (PBP2a) encoded by the mec A gene, inserted in the Staphylococcal Cassette Chromosome mec (SCC mec ) [ 12 , 13 ]. In addition to antimicrobial resistance, S. aureus is capable of producing a large number of virulence factors, such as toxins and enzymes, hemolysins (α, β, γ, and δ), Panton-Valentine Leucocidin (PVL), Staphylococcal Enterotoxins (SEs), exfoliative toxins A and B (ETA and ETB), toxic shock syndrome toxin (TSST-1), as well as the ACME gene, formed by the cluster arc and opp3 , responsible for increasing the pathogenicity of strains by improving their fitness and conferring the ability to survive in an acidic environment [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%